KEANEKARAGAMAN DAN KELIMPAHAN ANGGREK EPIFIT DI KAKI GUNUNG LIANGPRAN, KALIMANTAN TIMUR - Effendi, Surianto; Ariyanti, Nunik Sri; Chikmawati, Tatik (Research Center for Biology-Indonesian Institute of Sciences, 2019)
Liangpran Mountain is located within the Heart of Borneo (HoB) Conservation Area which has high biodiversity. The exploration of orchids has been carried out in several locations in the HoB region and recorded a high diversity of wild orchid. This research was conducted to explore and inventory the orchids from the foothill of Mount Liangpran, and record the diversity and abundance of epiphytic orchids in the study sites. This research was carried out by making track of exploration along the Nuyung river estuary to the Tebing Lapah. The richness and abundance data were collected in three plot of 1000 x 20 m. The host tree characteristics and distribution of epiphytic orchid on the host tree were recorded. Fourteen species orchids were collected, and the most dominant are Coelogyne asperata and Agrostophyllum stipulatum with an abundance of 23.53% each. The epiphytic orchids in host trees are spread from the zone II to V based on the Johansson?s sections, in which zone IV is the most diverse. Nine species of the host trees associated with the collected orchids were identified and grouped into five families. The characters of host trees are 7?57 m height,12?112 cm diameters, and 2 types of bark surfaces (rough and intermediate).